Treatment of Actinic Keratosis with Photodynamic Therapy Using Red or Green Light: A Comparative Study - Beata J. Osiecka; Piotr Nockowski; Jacek C. Szepietowski (Medical Journals Sweden, 2018)
Actinic keratosis (AK) is the most common in situ cancerous skin lesion. Compared with other approved treatment modalities photodynamic therapy is preferred by patients due to faster recovery and improved cosmetic outcome. However, pain during irradiation is an important drawback. The aim of this study was to compare the effectiveness and tolerability of topical aminolaevulinic acid-photodynamic therapy in the treatment of AK on the head using red and green light. Complete remissions after 3 sessions of photodynamic therapy at 2-week intervals following 9 months of observation were 91.67% for red light and 86.67% for green light (difference not significant). The mean pain value was significantly greater in areas irradiated with red light compared with green light for all 3 sessions. This comparative study demonstrates that aminolaevulinic acid-photodynamic therapy with green light is of similar efficacy as that with red light in the treatment of middle/moderate AK, but causes less pain.